Can the Artificial Release of Fluorinated Gases Offset Global Cooling Due to Supervolcanic Eruptions? - Yangyang Xu; Nathanael P. Ribar; Jeffrey Sachnik; Gunnar W. Schade; Andrew John Lockley; Yi Ge Zhang; Pengfei Yu; Jianxin Hu; Guus J. M. Velders (Atmosphere)
Large volcanic eruptions, such as the prehistoric Yellowstone eruption, induce abrupt global cooling—by some estimates at a rate of ~1 °C/year, lasting for more than a decade. An abrupt global cooling of several °C—even if only lasting a few years—would present immediate, drastic stress on biodiversity and food production. This cooling poses a global catastrophic risk to human society beyond the immediate and direct impact of eruptions. Using a simple climate model, this paper discusses the possibility of counteracting large volcanic cooling with the intentional release of greenhouse gases. Longer-lived compounds (e.g., CO2 and CH4) are unsuitable for this purpose, but selected fluorinated gases (F-gases), either individually or in combinations, could be released at gigaton scale to offset large volcanic cooling substantially. We identify candidate F-gases (e.g., C4F6 and CH3F) and derive radiative and chemical properties of ‘ideal’ compounds matching specific cooling events. Geophysical constraints on manufacturing and stockpiling due to mineral availability are considered, alongside technical and economic implications based on present-day market assumptions. The effects and uncertainty due to atmospheric chemistry related to aerosol injection, F-gases release, and solar dimming are discussed in the context of large volcanic perturbation. The caveats and future steps using more complex chemistry–climate models are discussed. Despite the speculative nature of the magnitude and composition of F-gases, our conceptual analysis has implications for testing the possibility of mitigating certain global catastrophic cooling risks (e.g., nuclear winter, asteroid impact, and glacier transition) via intentional intervention.